Urban Now A Human in the Face of Borderliness and Urbanisation in Juba, South Sudan - Kurcz, Maciej (International Relations in Asia, Africa and the Americas, 2021)
The subject of the study is the spontaneous city spreading process of Juba after the end of the civil war in South Sudan (2005). The book presents the complex dynamics of transformations within the new urban settings of post-war Juba. The viewpoint taken while describing these phenomena is the adaptation of an average migrant to a new urban environment. This was not an easy task. At that time the city was characterised by extremely harsh living conditions, harsh even for post-war South Sudan. Despite the difficulties, the city's development was visible. The phenomenon of borderlineness - the closeness of the state's borders - appeared to be helpful in this process. It influenced the effectiveness of human activities, it is an answer to the spontaneous city spreading processes - it brought danger, but most of all, infinite possibilities. The presented material comes from the author's ethnographic research conducted in Juba in 2007 and 2008.